Kajian kualitas air untuk menunjang perikanan budidaya Danau Moaat, Provinsi Sulawesi Utara - Paputungan, Firgiawan; Pangemanan, Novie P. L.; Tumbol, Reiny A.; Undap, Suzanne L.; Tumembouw, Sipriana S.; Rantung, Steelma V. (Universitas Sam Ratulangi, 2022)
The purpose of this study was to measure several physical and chemical parameters of Mooat Lake waters and to assess the feasibility of water quality in Mooat Lake waters to support aquaculture.Primary data were obtained from direct sample measurements in the field (in situ) and laboratory analysis. In situ sample measurement data consisted of temperature, degree of acidity (pH), dissolved oxygen (DO), and turbidity. Sampling of water at all research stations used a modified bottle that was labeled accordingly as a water sample holder. After the water sample is taken in the field, stored in a cooler, then taken to the Laboratory of Environmental Health Engineering and Disease Control (BTKLPP) class 1 Manado and the Manado BARISTAND Laboratory for examination of levels of Nitrite (NO2), Nitrate (NO3), Ammonia (NH3) , and Phosphate (PO4). Based on research data of several water quality parameters measurements and analysis show that temperature (26,17oC), Turbidity (11,20 NTU), pH (5,6), DO (8,31), nitrite (0,04005 mg/l), nitrate (0,705 mg/l), ammonia (0,145 mg/l), and phosphate (1,005 mg/l). These results show that the waters of Mooat Lake is still feasible and meets the water quality standard values to support aquaculture activities. Furthermore, it is strengthened by the analysis of the suitability of the location for the development of aquaculture which shows that the water quality conditions of Mooat Lake are classified as suitable.